Interactions between normal and transformed epithelial cells: Their contributions to tumourigenesis. - Hogan, C.; Kajita, M.; Lawrenson, K.; Fujita, Y. (International Journal of Biochemistry & Cell Biology, 2011)
During the initial stages of carcinogenesis, neoplastic transformation occurs in single epithelial cells and the transformed cells proliferate while being surrounded by normal epithelia. In Drosophila, normal and transformed epithelial cells compete with each other for survival, a process called cell competition. However, it was not known whether comparable phenomena also occur in mammals. Recently, several reports have shown that the interaction between normal and transformed epithelial cells causes various phenomena in mammals. For example, with elaborate cell culture systems that express oncoproteins or knockdown tumour suppressor proteins in an inducible manner, certain types of transformed cells have been shown to be apically eliminated from normal epithelial layers in an apoptosis-dependent or -independent manner. During the process of apical extrusion, various signalling pathways are modulated in transformed cells located within the normal epithelium, indicating that the presence of surrounding normal epithelial cells affects the behaviour and fate of transformed cells. Recent studies in mice have also shown that normal and transformed cells can compete with each other for survival during several processes such as liver regeneration. In this review, we will introduce these recent publications on interactions between normal and transformed mammalian epithelial cells. Furthermore, we will discuss how these studies can potentially lead to identification of biomarkers for precancerous cells and to invention of novel types of cancer prevention and treatment.